2016
DOI: 10.1200/jop.2015.009068
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Therapy for Limited-Stage Small-Cell Lung Cancer

Abstract: Limited-stage small-cell lung cancer (SCLC) occurs in only one third of patients with SCLC, but it is potentially curable. Combined-modality therapy (chemotherapy and radiotherapy) has long been the mainstay of therapy for this condition, but more recent data suggest a role for surgery in early-stage disease. Prophylactic cranial irradiation seems to improve outcomes in patients who have responded to initial therapy. This review addresses the practical aspects of staging and treatment of patients with limited-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
0
19
0
2
Order By: Relevance
“…2 Response rates approximate 60% to 70% with initial therapy in limited-stage disease (disease for which the treatment standard remains chemotherapy with four to six cycles of cisplatin and etoposide and concurrent radiation therapy, followed by prophylactic cranial irradiation in responders). 2,3 For the 60% to 70% of patients presenting with extensive-stage disease at diagnosis, standard treatment includes four to six cycles of cisplatin or carboplatin and etoposide or irinotecan (clinical trials have not supported the superiority of irinotecan over etoposide in the United States and Europe), followed by consideration for prophylactic cranial irradiation and thoracic radiation therapy in responders. 2,[4][5][6] The median overall survival (OS) approximates 20 months in limited-stage SCLC, with estimated 5-year survival rates of , 15%, whereas the median OS is approximately 8 to 12 months for extensivestage SCLC, with 5-year survival rates of , 2%.…”
Section: Introductionmentioning
confidence: 99%
“…2 Response rates approximate 60% to 70% with initial therapy in limited-stage disease (disease for which the treatment standard remains chemotherapy with four to six cycles of cisplatin and etoposide and concurrent radiation therapy, followed by prophylactic cranial irradiation in responders). 2,3 For the 60% to 70% of patients presenting with extensive-stage disease at diagnosis, standard treatment includes four to six cycles of cisplatin or carboplatin and etoposide or irinotecan (clinical trials have not supported the superiority of irinotecan over etoposide in the United States and Europe), followed by consideration for prophylactic cranial irradiation and thoracic radiation therapy in responders. 2,[4][5][6] The median overall survival (OS) approximates 20 months in limited-stage SCLC, with estimated 5-year survival rates of , 15%, whereas the median OS is approximately 8 to 12 months for extensivestage SCLC, with 5-year survival rates of , 2%.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in addition to concurrent chemoradiotherapy, aggressive surgery is beneficial to potentially curable limited-stage SCLC. [ 16 ] Besides, an accurate staging is critical before surgery. Multidisciplinary therapies make more patients eligible for surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Currently the National Comprehensive Cancer Network (NCCN) recommends that the primary treatment of medically inoperable T1-T2 N0 patients can include Stereotactic Body Radiation Therapy (SBRT), but data is limited. 10 For operable patients, lobectomy with adjuvant therapy is an option which is primarily based off a National Cancer Database (NCDB) study performed by Yang et al 11 Several institutions have reported their experience with SBRT in early stage SCLC. [12][13][14] SBRT is an advanced method of radiotherapy delivery characterized by high dose per fraction and precise tumor targeting given over a limited number of fractions (typically 5 or less).…”
Section: Introductionmentioning
confidence: 99%